«TRANSPORT MASALASINI DASTLABKI YECHIMINI ANIQLASH USULLARI» MAVZUSIDA BUMERANG METODIDAN FOYDALANISH ORQALI TALABALARNI FAOLLASHTIRISH METODIKASI - Yusupov, F.; Yusupov, D.F.; Raximova, L.S.; Xaitbayeva, D.Z. (SCIENCE and SOCIETY, 2025)
This article explains the use of advanced pedagogical technologies to teach students methods for solving transportation problems in an understandable and engaging way. Teaching sessions that incorporate various interactive methods increase the effectiveness of students’ understanding, creating a basis for their active participation in the lesson. The article describes a mechanism developed to activate students through the use of the boomerang method when teaching approaches to solving transportation problems.
Keywords: interactive method; algorithm; boomerang; brainstorming; pedagogical technology; transportation problem